Enhancing trust and privacy in iot ecosystems with the distributed trust and privacy consensus framework - Priyadarashini, Sushma; T, Anuradha (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
In the contemporary digital landscape, the proliferation of wireless sensor networks (WSNs) and the internet of things (IoT) has revolutionized the way we interact with the physical world, offering unprecedented opportunities for automation and data-driven decision-making. However, this rapid expansion has also introduced significant challenges in terms of ensuring network security, maintaining user privacy, and establishing trust among devices. To address these critical issues, this paper introduces the distributed trust and privacy consensus framework (DTPCF), a novel methodology designed to strengthen trust and privacy within IoT ecosystems through a consensus-based approach. The DTPCF pioneers a distributed mechanism for trust management that evaluates and establishes the reliability of nodes democratically and transparently, thereby enhancing the robustness and scalability of IoT systems against malicious activities. Moreover, the framework integrates privacy preservation directly into the consensus process, employing state-of-the-art cryptographic techniques and protocols to protect sensitive data during transmission and decision-making phases. Through empirical analysis, the efficacy of the DTPCF is validated across various operational scenarios, demonstrating its effectiveness in enhancing network security, privacy, and trust. Performance metrics such as throughput, energy consumption, and node-level security are meticulously evaluated, providing comprehensive insights into the framework's capabilities and potential for real-world implementation.